MOLYBDENUM FLAT COIL FILAMENT FOR SAMPLE INTRODUCTION AND MULTIELEMENTAL DETERMINATION BY SMALL-SIZED ELECTROTHERMAL VAPORIZATION CAPACITIVELY COUPLED MICROPLASMA OPTICAL EMISSION SPECTROMETRY - CADAR, Sergiu; DUDU, Adrian-Ioan; PETREUS, Dorin; ANGYUS, Simion Bogdan; FRENTIU, Maria; COVACI, Eniko (Studia Universitatis Babeș-Bolyai Chemia, 2025)
A novel small-sized electrothermal vaporization device including a molybdenum flat coil filament was studied for sample introduction into a capacitively coupled microplasma (SSETV-µCCP-OES) for the simultaneous multielemental determination of Cu, Zn, Pb, Cd, Hg, Se, Te, Sb and Bi by optical emission spectrometry. The limits of detection, obtained by this experimental setup were 2–25 times lower than those previously obtained using a Rh coil filament, ranging from 0.16 µg L–1 for Cd to 10.7 µg L–¹ for Se. This improvement was primarily attributed to the more efficient heating of the Mo flat coil filament compared to the Rh coil filament, considering that Rh has a lower melting point and therefore must be heated more gradually. Consequently, in the transient spectra recorded using the Mo flat coil filament the maximum signal intensities were observed earlier, ranging from 1.5 s for Hg to 3.3 s for Zn, compared to those obtained with the Rh coil filament, which ranged from 2.4 s for Hg to 5.3 s for Cu. The results demonstrate the strong analytical potential of the SSETV device with the Mo flat coil filament, for the simultaneous multielemental trace metal analysis.